Marine Arctic polygon distribution of Plain Sculpin (Myoxocephalus jaok) (Cuvier, 1829) - Lyman K. Thorsteinson (USGS Science Data Catalog, 2017)
Region(s) of distribution of Plain Sculpin (Myoxocephalus jaok) (Cuvier, 1829) in the Arctic as digitized for U.S. Geological Survey Scientific Investigations Report 2016-5038. For details on the project and purpose, see the report at https://doi.org/10.3133/sir20165038. Complete metadata for the collection of species datasets is in the metadata document "Dataset_for_Alaska_Marine_Fish_Ecology_Catalog.xml" at https://doi.org/10.5066/F7M61HD7. Source(s) for this digitized data layer are listed in the metadata Process Steps section. Note that the original source may show an extended area; some datasets were limited to the published map boundary. Distributions of marine fishes are shown in adjacent Arctic seas where reliable data are available. The data were clipped to show only the marine distribution areas although some species also may have an inland presence.